(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article is today in the day only really enlightened man a person value , national values , one word with in other words , his identity understanding , free and free in society living , independent of our country the world in the community to himself worthy place take over for dedication with Struggle it is mentioned that it is possible.